Iterative Decoding And Detection For CDMA Systems On Non-Gaussian Channels - Ku, Ivan Chui Choon (2006)
The presence of impulsive non -Gaussian noise in multiple access channels presents a challenge to the operation of iterative/turbo multiuser receivers without proper mitigating measures. Thus, the study is extended to impulsive non-Gaussian channels whereby it is found that the performance of Gaussian iterative/turbo multiuser receivers seriously degrades when the underlying noise density function departs from Gaussianity.